Management of procedural pain in preterm infants through olfactive stimulation with mothers’ milk: A pilot study - De Clifford-Faugère, Gwenaëlle; Aita, Marilyn; Héon, Marjolaine; Le May, Sylvie (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2019)
Introduction: Repeated and untreated pain can lead to long-term consequences in preterm infants, such as pain hypersensitivity and impaired motor and intellectual development. Studies on pharmacological and non-pharmacological interventions for pain management in preterm infants are limited. Thus, we piloted an intervention based on olfactive stimulation with mothers’ milk. Objective: To assess the feasibility, acceptability, and preliminary effects of an olfactive stimulation intervention with mothers’ milk for procedural pain in preterm infants. Methods: A pilot study was conducted with mothers, nurses, and preterm infants. Twelve preterm infants were familiarized to the odor of their mother’s milk 9 hours before heel prick. During heel prick, mothers’ milk odor was combined with standard care by placing a pad saturated with mothers’ milk beneath the infant’s nose. Pain was measured using Preterm Infant Pain Profile-Revised tool. Mothers (n=11) and nurses (n=20) completed questionnaires regarding feasibility and acceptability. Results: More than 80% of mothers and nurses reported that the olfactive stimulation intervention was feasible and acceptable. Time taken for preterm infants’ heart rate and oxygen saturation to return to the baseline was reduced and pain scores were lower when the mothers’ milk pad was placed at 1 millimeter(mm) of the infant’s nose. Discussion and conclusion: The olfactive stimulation intervention is feasible and acceptable for nurses and mothers. The observed preliminary effects suggest that a pad saturated in mother’s milk placed 1 mm from the preterm infants’ nose could reduce the pain response. A randomized clinical trial should be conducted to assess the effectiveness of this intervention.